Characterization of a high cadmium accumulating soil bacterium, Cupriavidus sp. WS2. (May 2020) - Shi, Zunji; Zhang, Zhengfeng; Yuan, Meng; Wang, Song; Yang, Mei; Yao, Qi; Ba, Wanni; Zhao, Jin; Xie, Bo
Abstract: Cadmium (Cd) is one of the most harmful heavy-metals, its accumulation in crops can lead to severe ecological and healthy problems. Bioremediation using microbes to remove Cd or reduce the bioavailability of Cd is considered as a promising approach for Cd pollution control. Here, we described the isolation and characterization of a high Cd-accumulating bacterial strain, Cupriavidus sp. WS2, from the heavy-metals contained soil at the Wuhan Iron and Steel Company area. WS2 can survive under the high Cd conditions and immobilize Cd by biosynthesizing intracellular Cd-containing nanoparticle inclusions. In the co-inoculation test WS2 also significantly decreased the accumulation of Cd in rice seedlings. All our results suggested that Cupriavidus sp. WS2 may harbor a great potential for the bioremediation applications of Cd pollution. Highlights: High Cd-resistant bacterial strains have been isolated from the Wuhan Iron and Steel Company area. Cupriavidus sp. WS2 can form intracellular Cd-containing nanoparticle inclusions under the high Cd conditions. Cupriavidus sp. WS2 significantly decreased the accumulation of Cd in rice seedlings.